The Influence of Work Motivation, Work Environment and Job Satisfaction on Employee Performance at CV Lanupi Bandung - Wulandari Gunawan; Yoyo Sudaryo; Gurawan Dayona Ismail; Andre Suryaningprang; Dadan Abdul Aziz (Syntax Idea)
Employee performance is an assessment of work results, and the quality of thinking, behavior and achievements of individuals or teams in achieving organizational goals. This is important to determine the effectiveness and performance of the organization to determine the quality, efficiency and performance of the work carried out by each employee, as well as providing feedback and direction that can improve their performance. Employee performance can be influenced by several factors including, Work Motivation, Work Environment and Job Satisfaction on Employee Performance, The research method used is a quantitative research method with a descriptive and verification approach. The sample in this study was a total sample with a total of 30 respondents. In this study the entire population was sampled, so it is said to be a saturated sample.The research results show that work motivation, work environment and job satisfaction influence employee performance partially or simultaneously with a coefficient of determination test value of 0.753 or 75% so it can be interpreted that 75% of CV. Lanupi (Y) employee performance can be explained by variables work motivation (X1), work environment (X2), and job satisfaction (X3).The research results show that: (1). Employee performance is in the poor category (2). Work Motivation is in the poor category (3) Work Environment is in the poor category (4). Job satisfaction is in the poor category (5). Partial research results show that work motivation influences employee performance (6).